Studi Komparatif Fatwa Majelis Ulama Indonesia, Nahdlatul Ulama, dan Muhammadiyah tentang Talak di Luar Pengadilan - Zahrul Fatahillah (Institut Agama Islam Al-Aziziyah Samalanga, 2023)
This research is motivated by the many decisions of the Syar'iyah Court and Religious Courts that decide cases of divorce three into one and cancel the divorce pronounced by the husband outside the Court. This research is a normative juridical research that uses a comparative approach, in order to compare legal opinions based on the fatwa of the Indonesian Ulema Council, Nahdlatul Ulama, and Muhammadiyah. These three institutions differ in their opinions on the legal status of divorce pronounced outside the court, the difference is due to different ways of determining the law, but there are similarities, namely recognizing that the utterance of divorce in court is valid and recognizing that the Religious Courts in Indonesia are institutions authorized to hear divorce cases.